Relationship between oral condition and psychomotor development in children aged 6 and 7 years - Rossmary Janelle Navarro Betetta; Guido Alberto Perona Miguel de Priego (Revista Cubana de Estomatología, 2022)
Introduction: Oral health is a current problem in society; preventive measures such as brushing techniques must be according to motor skills.